Impact of community strategy package on uptake of reproductive tract infections health services among young street females in the municipality of Eldoret, Kenya - C Violet Maritim; Anthony Wanyoro; John Maingi; Jackim Nyamari; Murima Ng'ang'a (BMJ Publishing Group, 2023)
Background: Despite the intervention of free medical care services for street children by a dedicated clinic in Eldoret municipality, health care service of young street females (YSFs) is still deficient. The present study aimed to evaluate the impact of the community strategy package on the uptake of reproductive tract infections (RTI) health services among the target population. Materials and methods: A pre-test-post-test quasi-experimental with a qualitative and quantitative approach was applied among the YSFs aged 10-24 years. The study used structured questionnaires and key informant interviews to collect data from the respondents. Results: The study enrolled a total of 77 young street females in Eldoret municipality. A significantly higher proportion of respondents reportedly first sought treatment for RTI at a health facility after the implementation of the community strategy package (97.1%) when compared to the proportion of respondents who first sought treatment at a health facility in the pre-intervention phase (51.0%)(p＜0.001). Early seeking of treatment improved significantly after the introduction of the intervention; 72.0% and 94.1% of the respondents sought treatment early during the pre-intervention and post-intervention phase, respectively (p ​= ​0.011). Conclusion: The study recommends the adoption of the community strategy as an intervention to increase the uptake of RTIs health services and promotion of the reproductive health of young street females.